2020
DOI: 10.1007/s13346-020-00715-6
|View full text |Cite
|
Sign up to set email alerts
|

Methylene blue-loaded niosome: preparation, physicochemical characterization, and in vivo wound healing assessment

Abstract: Following skin injury, the overproduction of reactive oxygen species (ROS) during the inflammatory phase can cause tissue damage and delay in wound healing. Methylene blue (MB) decreases mitochondrial ROS production and has antioxidant effects. The authors aimed to prepare MB-loaded niosomes using the ultra-sonication technique as a green formulation method. A Box-Behnken design was selected to optimize formulation variables. The emulsifier to cholesterol ratio, HLB of mixed surfactants (Span 60 and Tween 60),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 46 publications
3
61
0
Order By: Relevance
“…This study showed that MB-loaded niosome formulations had high encapsulation efficiency and acceptable stability. In addition, according to biochemical and macroscopic studies, the recovery rate of surgical wounds in the niosomal-treated group was higher than that of other groups [ 18 ].…”
Section: Niosomes As New Drug Delivery Systemsmentioning
confidence: 99%
“…This study showed that MB-loaded niosome formulations had high encapsulation efficiency and acceptable stability. In addition, according to biochemical and macroscopic studies, the recovery rate of surgical wounds in the niosomal-treated group was higher than that of other groups [ 18 ].…”
Section: Niosomes As New Drug Delivery Systemsmentioning
confidence: 99%
“…The healing of cutaneous wounds has four stages which are hemostasis, inflammation, proliferation and maturation [ 104 ]. Angiogenesis, which is the formation of new blood vessels, is an essential process during wound healing [ 105 ].…”
Section: Cholesterol-based Compounds In Transdermal Drug Deliverymentioning
confidence: 99%
“…The body’s defense system releases endogenous antioxidant that helps against overexpression of ROS. A number of exogenous antioxidants such as phenolic compounds, ascorbic acid and vitamin E also speed up wound healing processes [ 104 ]. An ideal wound dressing needs to keep the wound moist, minimize infection, reduce pain and increase the rate of healing [ 106 ].…”
Section: Cholesterol-based Compounds In Transdermal Drug Deliverymentioning
confidence: 99%
See 2 more Smart Citations